2023
DOI: 10.1002/2688-8319.12263
|View full text |Cite
|
Sign up to set email alerts
|

Spatial targeting of woodland creation can reduce the colonisation credit of woodland plants

Samuel Hughes,
William Kunin,
Guy Ziv
et al.

Abstract: Colonisation credit refers to the temporal lag between positive conservation actions and species' responses and may be one of the reasons we fail to meet short‐term conservation targets. This is particularly evident in woodlands which take decades to develop and harbour slow colonising species. Given global objectives to increase woodland cover, it is important to know the timeframe within which colonisation credit will be fulfilled. The colonisation of woodland plants was examined in recent woodlands, create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Unexpectedly, we found no influence of the surrounding landscape on species richness (specialists and generalists) or on the presence of the 10 most common specialists. This is contrary to previous studies linking plant richness (or occurrence) and distance to nearest woodland (Brunet et al, 2021;Hughes et al, 2023;Naaf & Kolk, 2015) or amount of woodland in the surrounding landscape (Jamoneau et al, 2011;Liira et al, 2012;Peña et al, 2011;Petit et al, 2004).…”
Section: Weak Effects Of Landscape Attributescontrasting
confidence: 99%
See 3 more Smart Citations
“…Unexpectedly, we found no influence of the surrounding landscape on species richness (specialists and generalists) or on the presence of the 10 most common specialists. This is contrary to previous studies linking plant richness (or occurrence) and distance to nearest woodland (Brunet et al, 2021;Hughes et al, 2023;Naaf & Kolk, 2015) or amount of woodland in the surrounding landscape (Jamoneau et al, 2011;Liira et al, 2012;Peña et al, 2011;Petit et al, 2004).…”
Section: Weak Effects Of Landscape Attributescontrasting
confidence: 99%
“…Those studies found that proximity to existing mature woodland is an important driver of plant colonisation and suggested that being more than 100 m away from nearest woodland may still incur a significant colonisation credit (i.e. lower richness than nearby old growth woodlands) after considerable time (~100 years; Brunet et al, 2021;Hughes et al, 2023). In comparison, woodland creation sites in this study were relatively isolated with a median distance of 153 m to the nearest broadleaf woodland (mean 218 m; range 7-1573 m), and 66% of woodlands over 100 m from the nearest woodland.…”
Section: Weak Effects Of Landscape Attributesmentioning
confidence: 99%
See 2 more Smart Citations